2014
DOI: 10.9775/kvfd.2014.11163
|View full text |Cite
|
Sign up to set email alerts
|

Broylerlerde Diyetteki Yağ Kaynaklarının Performans, Serum Kortikosteron Düzeyi, Antikor Titresi ve IFN-γ Gen Ekspresyonu Üzerine Etkileri

Abstract: The present study was performed to evaluate the effects of addition of fish oil, soybean oil and olive oil to diet on performance and immune response in broiler chickens. In a completely randomized design, 320 broiler chickens (Ross 308, 7 days old) were allocated to four dietary treatments (control and three vegetable oils), four replicates with 20 chicks per each. The results showed that body weight gain of chicks fed soybean oil was higher and feed conversion ratio was better than the other treatments in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…The result of this study was consistent with studies that reported that n-3 fatty acids was shown to enhance the antibody response of chicks to sheep red blood cells than the birds that were not treated with them (Sadeghi et al, 2014). Inclusion of flaxseed oil in diet improved immune response, probably because of the effects on long chain n-3 PUFA on eicosanoid levels (Swanson et al, 2012).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The result of this study was consistent with studies that reported that n-3 fatty acids was shown to enhance the antibody response of chicks to sheep red blood cells than the birds that were not treated with them (Sadeghi et al, 2014). Inclusion of flaxseed oil in diet improved immune response, probably because of the effects on long chain n-3 PUFA on eicosanoid levels (Swanson et al, 2012).…”
Section: Resultssupporting
confidence: 90%
“…Cholesterol level was the highest in chickens fed palm oil and the lowest in those received olive oil. In contrast to our finding, researchers who found that diets containing different lipid sources did not affect blood cholesterol values (Sadeghi et al, 2014;Moslehi et al, 2016). In general, these results agree with the findings of other authors who reported changes in the concentration of serum lipids of chickens with the dietary lipid sources differing in their degree of saturation (Adeyemi et al, 2016;Tari et al, 2020).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation